Omental whirl associated with bilateral inguinal hernia: a case report - Silva, Elsa (2014)
INTRODUCTION: Torsion of the omentum is a rare cause of abdominal pain. It is clinically similar to common causes of acute surgical abdomen and is often diagnosed during surgery. Inguinal hernia is a common condition but not frequently related with torsion of the omentum. CASE PRESENTATION: A 40-year-old Caucasian man came to our emergency department with abdominal pain of the left quadrant and abdominal distension for 2 days. His medical history included an untreated left inguinal hernia in the last year. Computed tomography revealed densification of mesocolon with left omentum "whirl" component and other signs of omental torsion. During an exploratory laparoscopy, a wide twist of his omentum with necrotic alterations that extended to the bilateral inguinal hernial content was observed. Omentectomy and surgical repair of bilateral inguinal hernia were performed. CONCLUSIONS: Torsion of the omentum is a rare entity and usually presents a diagnostic challenge. The use of abdominal computed tomography can help diagnosing torsion of the omentum preoperatively and, thus, prevents a surgical approach. Nonetheless, some cases of torsion of the omentum require surgical repair. Accordingly, a laparoscopic approach is minimally invasive and efficient in performing omentectomy.